TOURISM MANAGEMENT EXPLAINED BY THE CORRELATION BETWEEN THE AVERAGE TOTAL INCOME PER PERSON AND THE NUMBER OF OVERNIGHT STAYS IN ACCOMMODATION UNITS - Alina GHEORGHE (Business Excellence and Management)
In Romania’s tourism industry, in the last decade, following the European trend, small dimensioned accommodation units have appeared, bearing the name of boutique guesthouses or boutique hotels, depending on their accommodation capacity. The boutique guesthouses offer both accommodation services in rooms with traditional Romanian boyar characteristics, with Saxon and Szechuan influences, as well as food services with the same culinary characteristics. A particularity of these accommodation units is that each room had been furnishing according to a traditional noble theme, using either furniture that has been produced in Romanian workshops. Roomꞌ s names have been inspired by the woody essences that can be found in the Romanian forests and a large part of the furniture is made of cherry, beech, fir, oak, elm wood. The specific architecture of the accommodation units has been established in 18th century specific to the rococo and baroque style, predominantly found in buildings constructions in Romanian towns where niche tourism is a small part of mass tourism industry.